2018
DOI: 10.1016/j.bjm.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacterial communities and characterization of antimicrobial strains from cave microbiota

Abstract: In this study for the first-time microbial communities in the caves located in the mountain range of Hindu Kush were evaluated. The samples were analyzed using culture-independent (16S rRNA gene amplicon sequencing) and culture-dependent methods. The amplicon sequencing results revealed a broad taxonomic diversity, including 21 phyla and 20 candidate phyla. Proteobacteria were dominant in both caves, followed by Bacteroidetes, Actinobacteria, Firmicutes, Verrucomicrobia, Planctomycetes, and the archaeal phylum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 37 publications
8
30
0
Order By: Relevance
“…Our study has revealed 94.44% of the proteobacterial community was represented by the class Gammaproteobacteria. These findings were consistent with the previous cultivation-based studies where class Gammaproteobacteria were shown to constitute the major bacterial population (Banerjee & Joshi, 2016;Yasir, 2018). For instance, bacterial diversity study on the Meghalayan caves in North-East India, exposed thirty-two different cultivable bacterial species belonging to sixteen different genera where majority belongs to Pseudomonas and Bacillus (Banerjee & Joshi, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study has revealed 94.44% of the proteobacterial community was represented by the class Gammaproteobacteria. These findings were consistent with the previous cultivation-based studies where class Gammaproteobacteria were shown to constitute the major bacterial population (Banerjee & Joshi, 2016;Yasir, 2018). For instance, bacterial diversity study on the Meghalayan caves in North-East India, exposed thirty-two different cultivable bacterial species belonging to sixteen different genera where majority belongs to Pseudomonas and Bacillus (Banerjee & Joshi, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Proteobacteria phylum was dominated by the class Gammaproteobacteria with Pseudomonas sp. observed as the major genera in accordance to previous studies (Barton et al, 2004;Banerjee & Joshi, 2016;Yasir, 2018). Proteobacterial population seldom observed to be the dominant class in most of the cave bacterial diversity studies with the majority of the bacterial population has been shown as Actinobacteria (Axenov-Gribanov et al, 2016;Ghosh et al, 2016Ghosh et al, , 2017Lavoie et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Heterotrophic bacteria and fungi, constitute most of the biodiversity in caves and are ubiquitous in different cave habitats [43,5]; actinobacteria involved in biomineralization processes are common [44,45,46], and Bacillus and Paenibacillus occurrence has been frequently reported [47,48].…”
Section: Discussionmentioning
confidence: 99%